Strategi Pemasaran Digital (Instagram) terhadap Peningkatan Penjualan Pada Kedai 2 Putri di Desa Sipodeceng Kabupaten Sidenreng Rappang (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2025)
This study aims to analyze digital marketing strategies through Instagram to increase sales at the SME Kedai 2 Putri in Sipodeceng Village, Sidenreng Rappang Regency. The background of the study is based on the phenomenon of the increasing use of social media as a means of business promotion, especially among SMEs who need effective strategies to reach a wider consumer base. This study uses a qualitative approach with a descriptive method, where data is collected through interviews, observations, and documentation involving the owner, employees, and customers of Kedai 2 Putri. The results show that the digital marketing strategy implemented through Instagram includes four main indicators, namely content creation, content sharing, building interactions (connecting), and community building. Of these four indicators, content creation is the most dominant factor in attracting consumer interest and strengthening brand image, because attractive product visuals and consistent uploads have been proven to increase interaction and encourage purchasing decisions. In addition, the digital marketing strategy is also strengthened by elements of the marketing mix (7P) which include product, price, place, promotion, people, process, and physical evidence. Thus, this study confirms that optimal use of Instagram can increase visibility, customer engagement, and sales of MSMEs.